COVID-19 Therapies: Protease Inhibitions and Novel Degrader Strategies - Reboud-Ravaux, Michèle; El Amri, Chahrazade (Frontiers in Drug Discovery, 2022)
The global spread of severe acute respiratory syndrome corona virus-2 (SARS-CoV-2) variants is alarming. In addition to vaccines, effective antiviral agents are urgently needed to combat corona virus disease 2019 (COVID-19). In this review, we will give insights on several canonical approaches using current medicinal chemistry. They target host (TMPRSS2, cathepsins B/L, furin) and viral (3CLpro and PLPro) proteases involved in virus cell entry and virus production, respectively. Innovative mechanisms of drug action are now explored whereby the drug triggers a cellular event that reduces the level of disease-implicated protein or RNA. The potential therapeutic power of induced degradations of viral proteins by PROTACs and of RNA by RIBOTAC for the treatment of COVID-19 will be discussed. Degraders of host cell RNA-binding proteins (RNA-PROTACs) may also constitute a therapeutical opportunity. First applicated to oncology, these novel technologies may be of a particular interest to obtain therapeutics susceptible to act on mutated viruses.